INCREASE OF EFFICIENCY OF STRENGTHENING PROCESSING IN FRACTION - M.A. TAMARKIN; V.G. LEBEDENKO (Advanced Engineering Research)
The system of theoretical models past complex experimental check is developed. The given models can be used for increase of efficiency of strengthening processing in fraction at a stage of technological designing. On the basis of the offered system the technique of optimization of technological processes is developed and created SAPR TP processings in fraction.